(untitled) (Jurnal Bahasa, 2006)
This research has been carried out using the componential analysis to analyse every synonym. This componential analysis is aimed at analyz-ing and comparing the synonym of every word according to the number offeatures shared. Words which have high degree ofsynonymy are more likely to share many features in contrast to words of low degree of syn-onymy. The synonym of every word then is ascertained in sentences, using the substitution method, paradigmatically. Many types ofsentences have been chosen to provide various situational contexts. This analysis enables the research to reveal how far these synonyms shares meanings with the samples. Based on substitution in sentences, it is clear that the degree of synonymy for every word varies according to the sentences. Words which are absolutely synonymous in sentence A becomes non-synonymous in sentence B. This finding proves that the degree of syn-onymy of words is greatly influenced by the situational contexts or con-textual meaning of the varied sentences. When and where a word is regarded as synonym depends on the situational context of a sentence. Besides that this research also reveals that the number of absolute syn-onym words are very limited in number and in scope. In fact, there are nouns which have no absolute synonym words that are interchangeable without deviating from the original meaning of the sentences.